The Influence of Service Quality, Trust, and Customer Satisfaction on Customer Loyalty at PT Bank Rakyat Perekonomian Central Artha, Tegal City - Mahardina Yunidar RAHMA; Tabrani TABRANI; Sari WIYANTI (International Journal of Environmental, Sustainability, and Social Science, 2025)
The purpose of this study was to determine whether there is an effect of service quality (X1) on customer loyalty (Y), the effect of trust (X2) on customer loyalty (Y), the effect of satisfaction (X3) on customer loyalty (Y), and to find out how much service quality (X1), trust (X2), and satisfaction (X3) together on customer loyalty (Y). The method used in this research is a survey method with a quantitative approach through multiple linear regression analysis. The number of samples was 100 respondents who were customers of pt central artha people's economy bank in tegal city. The results showed that the service quality variable (X1) had a positive and significant effect on customer loyalty. The trust variable (X2) has a positive and significant effect on customer loyalty. While the satisfaction variable (X3) has a positive and significant effect on customer loyalty. Simultaneously, it shows that the three independent variables have a significant effect on customer loyalty pt central artha people's economy bank tegal city.